Be a triangle : how I went from being lost to getting my life in shape - Singh, Lilly, 1988- (Ballantine Books, 2022)
"An honest, funny, and inspiring primer on learning to "come home" to your truest and happiest self from the New York Times bestselling author of How to Be a Bawse. With the signature blend of vulnerability, wisdom, and humor that has endeared her to millions of fans, Lilly Singh offers a fresh take on how to feel fulfilled and find happiness in the face of life's challenges. Everyone knows that sometimes, life just sucks--Lilly's new book is here to provide a safe space where readers can learn how to create a sense of peace within themselves independent of external markers of success. Chatty and profound, spunky and real as hell, Singh is the perfect confidant, pep-talk-giver, and deep diver into how meditation, self-acceptance, our relationships and true gratitude can improve our lives. Without sugarcoating what it's like to face adversity--including Lilly's intensely personal struggles with identity, success, and self-doubt--this book teaches readers to "unsubscribe" from cookie-cutter ideals and to let go of societal expectations for what success looks like. Lilly instructs her readers to "be a triangle:" you must build a solid foundation for your life, one that can be built upon, but never fundamentally changed or destroyed. As Lilly puts it, we must always find a way to come home to ourselves -- "we must create a place, a set of beliefs, a simple set of priorities to come back to should life lead us astray, which it will." Like a wise, empathetic friend who always keeps you honest, Lilly pushes you to adjust your mindset and change the conversations you have with yourself. The result is a deeply humane, entertaining, and uplifting guide to befriending yourself and becoming a true "miracle for the world.""--